Strategi Guru Pendidikan Agama Islam dalam Pembiasaan Ibadah Pada Siswa di SMP Muhammadiyah 57 Medan - Silvia Febrianti; Mario Kasduri (Al-Ulum: Jurnal Pendidikan Islam, 2023)
The purpose of this study is to explain what strategies are used by Islamic education teachers in the habituation of worship, the process of implementing the habituation of worship and the success of the strategies used. The results of this study can be concluded that teachers use several strategies in worship habituation, the strategies used can form awareness and discipline in worship in students at SMP Muhammadiyah 57 Medan.